Investigating the Interaction of IAA and NaCl on the Early Growth of Acacia senegal (L.) Willd and Balanites aegyptiaca (Linn) Del. in Semi-arid Area of Sokoto, Nigeria - Igbokwe, G. O.; Bello, A. G.; Isah, A. D.; Audu, M. (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
Two important forest tree species adapted to the semi-arid environment of Sokoto, Nigeria, are Acacia senegal and Balanites aegyptiaca. The purpose of this experiment was to see how these species reacted to hormones (Indole-3-acetic acid IAA) and salt (NaCl). The plants were grown in soil from two sites in Dabagi research farm of Usmanu Danfodiyo University, Sokoto, with salt levels (2.0 and 3.0dS/m), and hormone was administered both at germination and early growth stages. The interaction effect enhanced leaf and relative growth rates in both plants, according to the results. This strategy could be utilised to help certain tree species grow and establish in semi-arid areas. The species developed using this technique can also be incorporated into land reclamation projects for the promise this research has indicated.